Abnormality in optimal forest management by indigenous people in deforestation - A. Mutolib; Y. Yonariza; A. Rahmat (Global Journal of Environmental Science and Management)
BACKGROUND AND OBJECTIVES: Deforestation threatens 120.5 million hectares of forest, and it occurs at a rate of 115 thousand hectares per year.  Economic needs and livelihoods encourage people to cut and farm forest areas. Deforestation is considered to be a random and unstructured process that does not involve indigenous people.  This research found that indigenous people and various other parties are continuously involved in forest land encroachment. Social networks have facilitated indigenous people and encroachers (buyers of forest land). This research aims to identify the actors involved in forest encroachment and the social network structure in the deforestation process in the production forest of Dharmasraya, Indonesia.METHODS: This study employs an ethnographic case study approach to understanding the drivers of deforestation in the Production Forest Management Unit of Dharmasraya.  The Production Forest Management Unit of Dharmasraya covers an area of 33,550 hectares. In customary law, the production forest is owned by four indigenous communities from the Nagari (villages): Bonjol, Abai Siat Nagari Sikabau, and Sungai Dareh. In this research, the data were collected through interviews that asked the respondent to report on those with whom she/he shared particular relations.  Primary data were collected using in-depth interviews employing the snowball sampling method. The data collection used interview guides relating to the actors involved in forest sales and the deforestation process.  Key informant interviews involving 34 key informants were conducted with traditional leaders, representatives of a lineage unit (Ninik Mamak) and adat functionaries (Datuak customary authorities), Wali Nagari (village chiefs), local institutional leaders, the government, companies, and those holding concessions. The secondary data were collected from relevant agencies in the research area.  The data were analyzed using descriptive–qualitative tools. FINDINGS: Three parties are interested in forest production, namely, the local indigenous people, the companies, and the government and each parties claims the production forest because each party sees itself as being the most eligible for forest ownership; this causes an overlap of forest management and ownership among the actors. The indigenous people have become the most powerful party in the ownership of the production forest. The claims of ownership of forests as customary forests have caused the traditional authorities to sell forests massively. The land sale price varies according to the position of the forest and its distance from villages, the topography, and the access. Ulayat (forest) land is considered cheap, ranging between USD 300 and USD 1,300 per hectare, including the Alas hak.  The Alas hak is a signed letter showing that the forest land or communal land has been sold to someone else. There are three models of ulayat forest land selling: selling by the customary authorities, selling through a broker, and selling by local people. The research has identified 40 actors involved in production forest management in Dharmasraya.  Eight actors were not involved in deforestation or ulayat forest selling. Ten actors were involved in deforestation and ulayat forest selling indirectly, and 22 actors were directly involved in deforestation through forest selling.CONCLUSION: Deforestation occurred because the indigenous people sold forest land massively. The sale of the land claimed as ulayat forest is not restricted; anyone interested in opening a plantation in a forest area can buy the land from the customary authorities. Hence, deforestation has occurred as part of a systematic process involving critical figures in the community. Ulayat forest land sales involved government officers, such as high-ranking police officers and army personnel, and entrepreneurs, officials, civil servants, and other parties who supposedly understand forestry law. The study also confirmed that the economic factors driving deforestation are facilitated by the social networks between indigenous people and the people holding power. The findings of this study contradict the general fact that indigenous people can manage forests sustainably.